Friend or Foe? Chloride Patterning in Halophytes. (February 2019) - Bazihizina, Nadia; Colmer, Timothy D.; Cuin, Tracey Ann; Mancuso, Stefano; Shabala, Sergey
Abstract : In this opinion article, we challenge the traditional view that breeding for reduced Cl − uptake would benefit plant salinity tolerance. A negative correlation between shoot Cl − concentration and plant biomass does not hold for halophytes – naturally salt tolerant species. We argue that, under physiologically relevant conditions, Cl − uptake requires plants to invest metabolic energy, and that the poor selectivity of Cl − -transporting proteins may explain the reported negative correlation between Cl − accumulation and crop salinity tolerance. We propose a new paradigm: salinity tolerance could be achieved by improving the selectivity of some of the broadly selective anion-transporting proteins (e.g., for NO3 − > Cl − ), alongside tight control of Cl − uptake, rather than targeting traits mediating its efflux from the root. Highlights: Interest in the Cl − aspect of salinity tolerance has traditionally focused on non-halophytes. Knowledge of Cl − regulation in 'salt-loving' halophytes is limited, even though these plants thrive and survive at much higher external Cl − than non-halophytes and use Cl − for osmoregulation. Proteins catalysing root Cl − transport have recently been characterised in non-halophytes, but this knowledge needs to be extended to halophytes. Of interest is that single amino acid polymorphisms in halophytic transporters alter their function compared to their non-halophytic homologues. Our understanding of post-translational regulation of anion channels in stomata is fairly advanced, but that of root Cl − transport remains elusive. The calcineurin B-like protein (CBL)–CBL-interacting protein kinase (CIPK) network regulates several ion transport systems in plants. Does it also modulate Cl − transport?